2020
DOI: 10.1021/acsomega.0c02413
|View full text |Cite
|
Sign up to set email alerts
|

Soft Heteroleptic N-Heterocyclic Carbene Palladium(II) Species for Efficient Catalytic Routes to Alkynones via Carbonylative Sonogashira Coupling

Abstract: N , N ′-Substituted di-isopropyl ( NHC-1 ), benzyl-isopropyl ( NHC-2 ), and adamantyl-isopropyl ( NHC-3 ) benzimidazolium salts react with palladium(II) bromide in pyridine to afford the corresponding trans -dibromidopyridinepalladium(II) complexes Pd-C1 , Pd-C2 , and Pd-C3 in high yields. A distorted square planar geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“… e Heteroleptic N-heterocyclic carbene palladium(II) complexes (Pd–NHC–Py). 59 f THF was used as a solvent. …”
Section: Resultsmentioning
confidence: 99%
“… e Heteroleptic N-heterocyclic carbene palladium(II) complexes (Pd–NHC–Py). 59 f THF was used as a solvent. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Ali et al investigated the catalytic efficiency of heteroleptic NHC-pyridine-Pd(II) complexes derived from benzimidazole having adamantyl, benzyl and isopropyl substituents in carbonylative Sonogashira coupling of aryl iodides and aryl diiodides with aryl alkynes, alkyl alkynes, and dialkynes. [59] Structural studies indicated a distorted square planar geometry for the trans-dibromidopyridine palladium-(II) complexes. Based on the DFT quantum mechanical descriptors of the frontier orbitals complex 32 c owing to its inherent steric and electronic properties provided by the adamantly group was found to be the softest species and its high catalytic activity towards soft substrates like aryl iodides compliments the results.…”
Section: Sonogashira Couplingmentioning
confidence: 99%
“…Recently, Ali et al . investigated the catalytic efficiency of heteroleptic NHC‐pyridine‐Pd(II) complexes derived from benzimidazole having adamantyl, benzyl and isopropyl substituents in carbonylative Sonogashira coupling of aryl iodides and aryl diiodides with aryl alkynes, alkyl alkynes, and dialkynes [59] . Structural studies indicated a distorted square planar geometry for the trans ‐dibromidopyridine palladium‐(II) complexes.…”
Section: Cross‐coupling Reactionsmentioning
confidence: 99%
“…(NHC)palladium(II) complexes were used efficiently in different applications including carbonylative coupling and alkoxycarbonylation and aminocarbonylation reactions. [ 36–40 ] The activity of (NHC)palladium(II) complexes is connected to the bonding nature of the NHC ligands including a strong σ‐electron donation, as well as a significant π acidity and π basicity, contributing to the stability of the different intermediates of the catalytic cycle and preventing deactivation pathways such as the formation of inactive palladium black. [ 41,42 ] The stability of these complexes can be further enhanced by the thermodynamic chelate effect such as the case of the chelating bis(NHCs).…”
Section: Introductionmentioning
confidence: 99%